Motor training promotes both synaptic and intrinsic plasticity of layer V pyramidal neurons in the primary motor cortex. (26th December 2022) - Kida, H.; Kawakami, R.; Sakai, K.; Otaku, H.; Imamura, K.; Han, Thiri‐Zin; Sakimoto, Y.; Mitsushima, Dai
Abstract : Abstract: Layer V neurons in the primary motor cortex (M1) are important for motor skill learning. Since pretreatment of either CNQX or APV in rat M1 layer V impaired rotor rod learning, we analysed training‐induced synaptic plasticity by whole‐cell patch‐clamp technique in acute brain slices. Rats trained for 1 day showed a decrease in small inhibitory postsynaptic current (mIPSC) frequency and an increase in the paired‐pulse ratio of evoked IPSCs, suggesting a transient decrease in presynaptic GABA release in the early phase. Rats trained for 2 days showed an increase in miniature excitatory postsynaptic current (mEPSC) amplitudes/frequency and elevated AMPA/NMDA ratios, suggesting a long‐term strengthening of AMPA receptor‐mediated excitatory synapses. Importantly, rotor rod performance in trained rats was correlated with the mean mEPSC amplitude and the frequency obtained from that animal. In current‐clamp analysis, 1‐day‐trained rats transiently decreased the current‐induced firing rate, while 2‐day‐trained rats returned to pre‐training levels, suggesting dynamic changes in intrinsic properties. Furthermore, western blot analysis of layer V detected decreased phosphorylation of Ser 408–409 in GABAA receptor β3 subunits in 1‐day‐trained rats, and increased phosphorylation of Ser 831 in AMPA receptor GluA1 subunits in 2‐day‐trained rats. Finally, live‐imaging analysis of Thy1‐YFP transgenic mice showed that the training rapidly recruited a substantial number of spines for long‐term plasticity in M1 layer V neurons. Taken together, these results indicate that motor training induces complex and diverse plasticity in M1 layer V pyramidal neurons. Key points: Here we examined motor training‐induced synaptic and intrinsic plasticity of layer V pyramidal neurons in the primary motor cortex. The training reduced presynaptic GABA release in the early phase, but strengthened AMPA receptor‐mediated excitatory synapses in the later phase: acquired motor performance after training correlated with the strength of excitatory synapses rather than inhibitory synapses. As to the intrinsic property, the training transiently decreased the firing rate in the early phase, but returned to pre‐training levels in the later phase. Western blot analysis detected decreased phosphorylation of Ser 408‐409 in GABAA receptor β3 subunits in the acute phase, and increased phosphorylation of Ser 831 in AMPA receptor GluA1 subunits in the later phase. Live‐imaging analysis of Thy1‐YFP transgenic mice showed rapid and long‐term spine plasticity in M1 layer V neurons, suggesting training‐induced increases in self‐entropy per spine. Abstract : Abstract figure legend Schematic of motor training and rapid spine dynamics in M1 layer V neurons. Exercise training promotes physiological and morphological spine diversity. Red: glutamate and AMPA receptors. Blue: GABA and GABAA receptors.